Radiative decays of double heavy baryons in a relativistic constituent three-quark model including hyperfine mixing effects; Physical Review D; Vol. 81, iss. 11 - Branz T. Tanja; Faessler A. Amand; Gutsche Th. Thomas; Ivanov M. A. Mikhail A.; Korner J. G. Jurgen G.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Oexl B. Bettina (2010, 2010)
Title screen